Strategi Advokasi Kesehatan dalam Mendukung Program Pengendalian ISPA di Indonesia: (Studi Literatur) - Josepin Karolina; Windi Audina; Rifqa Masry; Iswar Saputra Nasution; Miftahurrahmah El Hayatli (Jurnal Kesehatan Amanah, 2026)
Background: Acute Respiratory Infections (ARIs) remain a significant public health issue in Indonesia, particularly among vulnerable groups such as toddlers. Efforts to control ARIs do not rely solely on health services but also require health advocacy to raise public awareness and secure support from various stakeholders. Objective: This study aims to analyze the health advocacy strategies used to support ARI control programs in Indonesia. Methods: This study employed a literature review using a descriptive qualitative approach. Data were obtained from ten scientific articles in Indonesian published between 2022 and 2026 and retrieved via Google Scholar. Data analysis was conducted using content analysis techniques. Results: The findings indicate that health advocacy strategies for ARI control are primarily implemented at the community level through health education, the use of health communication media, and community empowerment. These strategies have been shown to improve knowledge, awareness, and preventive behaviors regarding ARI. Training of health cadres and active community participation also play a role in supporting the success of ARI control programs. However, studies related to advocacy at the policy level including regulatory aspects and health budget support remain relatively limited. Conclusion: Health advocacy plays a crucial role in supporting ARI control by improving health literacy and community engagement. To ensure the sustainability of these programs, advocacy efforts must be strengthened at the institutional and policy levels.